EVALUATION OF WATER QUALITY IN PANCA JAYA VILLAGE BLUE LAKE AS A BASIS FOR SAFE TOURISM MANAGEMENT - Nabila Asa Dinina; Andi ’Afifatul Fathonah; Yenni Kusrini Abelia; Masitah Masitah (Universitas Medan Area, 2026)
The high recreational potential of Danau Biru in Panca Jaya Village a former mining site poses a risk of health hazards to visitors due to chemical contamination of the water. This study aims to evaluate the physical and chemical quality of Danau Biru’s water as a basis for recommendations on sustainable safety management of the tourist destination. This mixed-methods study employed purposive sampling in two zones (shore and center) with three replicates. Parameters were analyzed using descriptive and comparative methods in accordance with Ministry of Health Regulation No. 2 of 2023. Laboratory test results indicated extremely hyperacidic conditions with pH values ranging from 2.39–2.52 (shore) and 2.29–3.88 (center), far below the quality standard (6.0–9.0). Biochemical Oxygen Demand (BOD) values ranged from 3.68–4.96 mg/L (periphery) and 3.20–4.80 mg/L (center), exceeding the maximum limit of 3 mg/L. Meanwhile, Dissolved Oxygen (DO) was recorded at 4.1–4.6 mg/L, still meeting the minimum criterion (≥ 4 mg/L). It is concluded that the water in Danau Biru does not yet meet recreational water quality standards; therefore, swimming is strongly discouraged to prevent the risk of skin irritation and chronic toxicity to visitors.